2018
DOI: 10.1002/nau.23896
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor hypertonicity in women with pelvic floor disorders: A case control and risk prediction study

Abstract: Aim Myofascial pelvic pain is a chronic and debilitating condition, sometimes associated with pelvic floor disorders (PFD) such as urinary incontinence, defecatory dysfunction or pelvic organ prolapse. Our aim was to identify risk factors in women with PFD and hypertonic pelvic floor, compared to controls without hypertonicity. Methods Case control study (2009‐2017) of patients with PFD and a diagnosis of hypertonic pelvic floor. Cases were matched with patients who presented with the same PFD but without pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…The improper PFM tonus leads to many disfunction [29,40]. Research indicates that increased tone of PFMs can prolong delivery course, while simultaneously favoring greater damage within them [41,42].…”
Section: Role Of Pelvic Floor Muscle In Continencementioning
confidence: 99%
See 1 more Smart Citation
“…The improper PFM tonus leads to many disfunction [29,40]. Research indicates that increased tone of PFMs can prolong delivery course, while simultaneously favoring greater damage within them [41,42].…”
Section: Role Of Pelvic Floor Muscle In Continencementioning
confidence: 99%
“…Research indicates that increased tone of PFMs can prolong delivery course, while simultaneously favoring greater damage within them [41,42]. PF hypertonicity frequently occurs in women with chronic pelvic pain [40], but may also leads to incontinence caused by increased intra-abdominal pressure. It is known that the persistent state of excessive muscle tension leads to a weakening of their strength and endurance.…”
Section: Role Of Pelvic Floor Muscle In Continencementioning
confidence: 99%
“…In this study, despite the fact that MD was not associated with depression, it is important to highlight higher rates were seen within the MD groups when compared to the CG and higher rates in both groups in the severe levels of depression. One study evaluated the predicted risk of developing hypertonia and myofascial pain within the PFM in women with UI and/or pelvic organ prolapse and found that depression was associated with hypertonia in these women 9 …”
Section: Discussionmentioning
confidence: 99%
“…It is unclear the combination of MD and psychological symptoms within women with UI. It is hypothesized that emotional aspects may drive towards a hypertonic PFM, as there has been demonstrated a greater tension within these muscles in women who are experiencing a high level of psychological stress 8 and increased risk of developing hypertonic PF in depressed women 9 . Understanding the association between UI and muscular/psychological aspects is essential as it might be considered that the emotional state of women with UI and MD may be different from those of women with UI without MD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation